Sabrina - Wick, Lori (Eugene, Or. : Harvest House Publishers, 2007)
Sabrina Matthews, a young prostitute, is befriended by a police officer and his wife, and comes to believe in Jesus, but when she arrives in Token Creek, Montana Territory, ready to make a fresh start, Sabrina finds herself falling for Pastor Rylan Jarvik and worries if he will accept her despite her past
Keywords: Prostitutes -- Fiction; Christian fiction